First Ever Organ Transplantation from A Brain-Dead Person in Bangladesh: A Successful Outcome of The Human Organ Transplantation Act (Community Based Medical Journal, 2024)
On the 19th of January 2023, a historic event took place in the field of medical practice and country’s healthcare system. A 20-year-old girl named Sarah Islam was pronounced clinically dead on Wednesday (18 January, 2023) while being treated at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, with her terminal illness as she has been suffering from tuberous sclerosis since her childhood. Her final act was termed 'heroic' by her attending physicians as she became the first patient in the country to donate her organs while being brain-dead. The next day in the early morning (19 January, 2023) doctors conducted the country's first-ever cadaveric kidney transplantation as taken from her. The recipients were two females in their 30s who were reportedly recovering well after the surgery. Those two surgeries were performed separately at Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital and the National Kidney Foundation Hospital in Dhaka. The Human Organ Transplantation Act (HOTA) officially came into force in Bangladesh on April 13, 1999, allowing organ donations from both living and brain-dead donors; after long discussion, some amendments were ratified by the Parliament in 2018. The Act places some legal requirements around the collection and preservation of human organs as well as ensuring their transplantation into a human body. Few years back, religious leaders came forward to issue a fatwa (religious approval) that recognize both living and brain death criteria and permit both living and brain-dead donors to donate organs for transplantation. Based on that fatwa and a long medical discussion the country’s parliament passed this Act. Enacting the HOTA shows an immense influence in our society on cadaveric organ donation and transplantation especially from brain-dead individuals, and we hope that this historic donation will create more awareness and pave a new path for organ donation campaign in the country in near future.CBMJ 2024 January: vol. 13 no. 01 P: 102-106